Nonequilibrium and quantum coherent phenomena in the electromechanics of suspended nanowires (Review Article) - Shekhter, Robert I.; Santandrea, Fabio; Sonne, Gustav; Gorelik, Leonid Y.; Jonson*, Mats (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Strong coupling between electronic and mechanical degrees of freedom is a basic requirement for the operationof any nanoelectromechanical device. In this Review we consider such devices and in particular investigatethe properties of small tunnel-junction nanostructures that contain a movable element in the formof a suspended nanowire. In these systems, electrical currents and charge can be concentrated to small spatialvolumes resulting in strong coupling between the mechanics and the charge transport. As a result, a varietyof mesoscopic phenomena appear, which can be used for the transduction of electrical currents intomechanical operation. Here we will in particular consider nanoelectromechanical dynamics far from equilibriumand the effect of quantum coherence in both the electronic and mechanical degrees of freedom in thecontext of both normal and superconducting nanostructures.